Shock-induced fan cowl separation during aeroengine windmilling at diversion from cruise - Sabnis, Kshitij; Babinsky, Holger; Boscagli, Luca; MacManus, David G.; Sheaf, Christopher T. (AIAA, 2025)
When a civil aircraft engine is operated at windmill during the cruise flight phase, there is supersonic flow acceleration around the leading edge of the fan cowl toward the external surface. The terminating normal shock wave can separate the turbulent boundary layer developing on this external surface. A series of experiments at a flight-relevant Reynolds number (1.2 million based on lip thickness) are performed in a quasi-two-dimensional wind tunnel rig to investigate the underlying flow physics. At a nominal inflow Mach number of 0.65 and a nacelle incidence angle of 4.5 deg, as the equivalent engine mass-flow rate is reduced, an increase in shock strength results in flow separation when the shock exceeds Mach 1.4. Over a 10% range in the notional engine mass-flow rate, the boundary layer developing on the external fan cowl thickens by a factor of three on the onset of separation. A reduction in the incoming Mach number from 0.65 to 0.60 weakens the shock wave and thus delays separation. An increase in surface roughness has no significant effect in situations where the boundary layer remains attached. However, for separated cases, an increased local roughness height causes a greater separation extent and a thicker boundary layer downstream of the shock wave.
Keywords: Aerospace & Aeronautics; 4001 Aerospace engineering; 4012 Fluid mechanics and thermal engineering; Aircraft Engines; Boundary Layer Separation; Freestream Mach Number; Aircraft Components and Structure; Shock Waves; Transonic Wind Tunnel; Separated Flows; Terminating Normal Shock; Nacelles